การศึกษาการแสดงออกของไธมิดิเลท ซินเทส ในการคาดเดาการได้ประโยชน์จากการรักษาเสริมด้วยยาเคมีบำบัดสูตรที่มีอ๊อกซาลิพลาตินร่วมกับฟลูโอโรยูราซิลเทียบกับการได้ฟลูโอโรยูราซิลเพียงชนิดเดียวในผู้ป่วยมะเร็งลำไส้ใหญ่ระยะที่สาม - ศิยามล มิ่งมาลัยรักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
BACKGROUND: Several trials demonstrated prognostic and predictive values of thymidylate Synthase (TS), targeted enzyme of Fluorouracil, in stage III colorectal cancer. We explored these values in correlation with disease free survival of adjuvant treatment in stage III colorectal cancer. METHODS: We reviewed medical records and collected tissue samples of patients who underwent curative resection for stage III CRC at King Chulalongkorn Memorial Hospital from 1 January 2005 to 31 December 2010. The immunohistochemistry method was used to detect the TS expression in all samples. We compared 5-year disease free survival (DFS) rates between patients receiving Fluoropyrimidine plus oxaliplatin (FU-Ox) and Fluoropyrimidine (FU) and, patients with low and high TS expression. RESULTS: Among 128 patients with stage III colorectal cancer, the TS expression intensity was high in 32.81%. With median follow up time of 5 years, patients with high TS expression had 5-yr DFS rates of 61.9% compared to 65.1% in patients with TS low expression, p=0.722. In FU-Ox group had 5 year DFS rate 70.6% compared to 59.7% in FU group, p=0.21. There was a trend toward better 5 year DFS rate for patients receiving FU-Ox compared to FU in patients with high TS expression (71.4% vs 52.4%, p=0.204). In low TS expression, it was 70% vs 62.5% in patients receiving FU-Ox and FU alone, (p=0.487), respectively. CONCLUSION: TS expression was a potential predictive factor for benefit of additional oxaliplatin to adjuvant fluorouracil in patients with colorectal cancer stage III.